PCR - McPherson, M. J (Taylor & Francis, 2006)
Previous edition: Oxford: BIOS, 2000; Includes bibliographical references and index; An introduction to PCR -- Understanding PCR -- Reagents and instrumentation -- Optimization of PCR -- Analysis, sequencing and in vitro expression of PCR products -- Purification and cloning of PCR products -- PCR mutagenesis -- Analysis of gene expression -- Real-time RT-PCR -- Cloning genes by PCR -- Genome analysis